2010
DOI: 10.1051/radiopro/2010014
|View full text |Cite
|
Sign up to set email alerts
|

Decision aiding handbooks for managing contaminated food production systems, drinking water and inhabited areas in Europe

Abstract: Three handbooks have been developed, in conjunction with a wide range of stakeholders to assist in the management of contaminated food production systems, inhabited areas and drinking water following a radiological incident. The handbooks are aimed at national and local authorities, central government departments and agencies, emergency services, radiation protection experts, the agriculture and food production sectors, industry and others who may be affected. The handbooks include management options for appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…No radionuclide contamination was detected in drinking water. Intake via water was previously shown to be a small contributor (Nisbet et al 2010). Therefore, in the present study the most important pathway for horses was identified as the ingestion of radionuclide-contaminated feed.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…No radionuclide contamination was detected in drinking water. Intake via water was previously shown to be a small contributor (Nisbet et al 2010). Therefore, in the present study the most important pathway for horses was identified as the ingestion of radionuclide-contaminated feed.…”
Section: Discussionmentioning
confidence: 92%
“…The hexacyanoferrate compound, Prussian blue, is a radiocesium binder that is added to farm animal feed to reduce the transfer of radiocesium to animal products by reducing its absorption in the gut (IAEA 1997). Ammonium-hexacyanoferrate (AFCF), the commonly used form for remediation, was used extensively after the Chernobyl accident in Russia, Ukraine, and Belarus as well as in western European countries, including Norway and Sweden, and was shown to be very effective for animal use (Pearce 1994;Nisbet et al 2010). Moreover, the acceptability of these strategies for Japanese farmers also needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The hexacyanoferrate compound, Prussian blue, is a radiocesium binder, which is added to the feed of farm animals to reduce radiocesium transfer to milk and other animal products by reducing absorption in the gut (IAEA 1997 ). Ammonium-hexacyanoferrate (AFCF), the commonly used form for remediation, was used extensively after the Chernobyl accident in Russia, Ukraine, and Belarus as well as in Western European countries, including Norway and Sweden, and was shown to be the most effective for animal use (Pearce 1994 ;Nisbet et al 2010 ). Moreover, the acceptability of these strategies for Japanese farmers also needs to be investigated, and (3) Collateral safety of animal products: to produce milk without disrupting normal farming practices, "Clean feeding" management has been considered feasible and suitable.…”
Section: Discussionmentioning
confidence: 99%
“…To deal with this, ERMIN and AGRICP will be enhanced with an optimisation wizard that guides the user through the many possible countermeasure options to select those which might be best in that given situation. The optimisation wizard will be realised as a knowledge data base which contains information from the European handbooks for managing contaminated food production systems and inhabited areas in Europe [8]. In this respect, the two simulation models will be further refined and made more and more user friendly.…”
Section: Conclusion and Further Developmentmentioning
confidence: 99%